International Symposium on Electromagnetic Compatibility 1992
DOI: 10.1109/isemc.1992.626103
|View full text |Cite
|
Sign up to set email alerts
|

Cables and Connectors - Their Contribution To Electromagnetic Cohpatibility

Abstract: The use of screening components is to keep the emissions of disturbance sources separate from instrument circuits. Their needed screening performance must depend also on the sensitivity and layout of the instrument circuit. An attempt will be made to reconcile screening measurements -related in the main to transfer impedance -with the need to design an instrument system for an environment specified in terms of radiated electromagnetic fields.After detailing some typical screening parameters in units that are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In [52] the 2.5 m bonding resistance is used as reference, and it is stated that this gives a good protection. Fowler [49] suggested that the transfer impedance of a connector for a single braided cable should be maximal 3 mup to 3 MHz, and then increasing with 20dB/decade. But comparing requirements for cables we observe a wide variation in levels, and no rationale.…”
Section: Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [52] the 2.5 m bonding resistance is used as reference, and it is stated that this gives a good protection. Fowler [49] suggested that the transfer impedance of a connector for a single braided cable should be maximal 3 mup to 3 MHz, and then increasing with 20dB/decade. But comparing requirements for cables we observe a wide variation in levels, and no rationale.…”
Section: Assembliesmentioning
confidence: 99%
“…In [47] a coaxial cable assembly is described and a measuring method for screening effectiveness of the assembly is given, using the line injection method. Fowler [49] gave an overview of the screening attenuation and transfer impedance concept applied to both cables and connectors, and even cabinets. He suggested to define connector grades, which should be included in standards.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of integration density, the interconnect connectors and cables are omnipresent and constitute a key element of electrical and electronic systems as automotive, aeronautics and spatial engineering's [1]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…The undesired environmental effects as the electromagnetic compatibility (EMC) perturbations must be taken into account during the design phase [1], [5], [6]. Therefore, behind the technological design progress and the increase of the design complexity, the electrical behavior and EMC prediction become a crucial problem and have an important role for the overall system performance [1], [5]- [7]. Different measurement and simulation techniques have been deployed as standard approaches for the EMC investigation [4], [5].…”
Section: Introductionmentioning
confidence: 99%